Ubiquinone-mediated coupling of NADH dehydrogenase to active transport in membrane vesicles from Escherichia coli. - Stroobant, P (1975)
Addition of ubiquinone-1 to E. coli ML 308-225 membrane vesicles dramatically increases coupling between NADH oxidation and active transport such that initial rates and steady-state levels of lactose and amino-acid accumulation are comparable to those observed during D-lactate oxidation. Similar but less dramatic effects are observed with the quinone and succinate or L-lactate. In the presence of NADH and ubiquinone-1, the vesicles also generate a membrane potential (interior negative) that is similar in magnitude to that observed in the presence of D-lactate. Stimulation of NADH-dependent transport by ubiquinone-1 cannot be accounted for by increased rates of oxidation of NADH, and the effect of the quinone on NADH-dependent lactose transport is not observed in vesicles depleted of NADH dehydrogenase activity. Thus, it is apparent that ubiquinone-1 shunts electrons from NADH dehydrogenase [NADH:(acceptor)oxidoreductase; EC 1.6.99.3] to the portion of the respiratory chain containing the energy-coupling site. The findings demonstrate unequivocally that inefficient coupling of NADH oxidation to active transport cannot be due to the presence of inverted vesicles. In addition, they provide further support for specific localization of the energy-coupling site.